2013
DOI: 10.1017/s0033291713000238
|View full text |Cite
|
Sign up to set email alerts
|

White-matter microstructure in previously drug-naive patients with schizophrenia after 6 weeks of treatment

Abstract: During the early phase of treatment, there is an acute reduction in WM FA that may be due to the effects of antipsychotic medications. However, it is not possible to entirely exclude the effects of underlying progression of illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 48 publications
6
53
0
2
Order By: Relevance
“…15 Until now, only a handful of longitudinal diffusion studies have been published, examining (short-term) effects of AP medication on microstructural WM (pre-post treatment measurements). [56][57][58][59] The results of the present study were supportive of an effect of (especially the highest) cumulative medication exposure levels on FA change over time, both in within-patients analyses and in between-group analyses based on AP exposure subgroups (with one-third of the patients in each subgroup). However, as the FA change in siblings, who were not using AP medication, was also significantly different from controls, AP exposure may be one of the contributing factors of microstructural WM alteration in patients with psychotic disorder.…”
Section: Methodological Considerationssupporting
confidence: 79%
“…15 Until now, only a handful of longitudinal diffusion studies have been published, examining (short-term) effects of AP medication on microstructural WM (pre-post treatment measurements). [56][57][58][59] The results of the present study were supportive of an effect of (especially the highest) cumulative medication exposure levels on FA change over time, both in within-patients analyses and in between-group analyses based on AP exposure subgroups (with one-third of the patients in each subgroup). However, as the FA change in siblings, who were not using AP medication, was also significantly different from controls, AP exposure may be one of the contributing factors of microstructural WM alteration in patients with psychotic disorder.…”
Section: Methodological Considerationssupporting
confidence: 79%
“…In order to avoid some confounding variables, studies in antipsychotic-naïve FEP patients are of particular interest. Studies in patients never treated with antipsychotics have shown abnormalities in inferior longitudinal fasciculus (Cheung et al, 2008; Liu et al, 2013), superior longitudinal fasciculus (Filippi et al, 2014; Guo et al, 2012; Mandl et al, 2013), cingulum (Wang et al, 2013b), fornix (Filippi et al, 2014; Guo et al, 2012), internal capsule (Guo et al, 2012), uncinate fasciculus (Mandl et al, 2013), genu and splenium (Cheung et al, 2008; Gasparotti et al, 2009), and occipital-frontal fasciculus (Cheung et al, 2008; Liu et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Since the scanning duration was about 10 min in this study, head motion is unlikely to be a major source of error. Potential effects of psychotropic medications cannot be fully resolved unless antipsychotic-naïve first-episode subjects are examined (Wang et al, 2013). Controlling for and examining the variance contributed by demographic factors revealed that diffusion measures were still important.…”
Section: Discussionmentioning
confidence: 99%